Adopting artificial intelligence in dental education: A model for academic leadership and innovation. Issue 11 (3rd July 2022) - Islam, Nadim M.; Laughter, Lory; Sadid‐Zadeh, Ramtin; Smith, Carlos; Dolan, Teresa A.; Crain, Geralyn; Squarize, Cristiane H.
Abstract: Introduction: The continual evolution of dental education, dental practice and the delivery of optimal oral health care is rooted in the practice of leadership. This paper explores opportunities and challenges facing dental education with a specific focus on incorporating the use of artificial intelligence (AI). Methods: Using the model in Bolman and Deal's Reframing Organizations, the Four Frames model serves as a road map for building infrastructure within dental schools for the adoption of AI. Conclusion: AI can complement and boost human tasks and have a far‐reaching impact in academia and health care. Its adoption could enhance educational experiences and the delivery of care, and support current functions and future innovation. The framework suggested in this paper, while specific to AI, could be adapted and applied to a myriad of innovations and new organizational ideals and goals within institutions of dental education.